Applications of wireless capsule endoscopy in pediatric age: an update - Fornaroli, Fabiola; Gaiani, Federica; Vincenzi, Francesca; Bizzarri, Barbara; Ghiselli, Alessia; Kayali, Stefano; Leandro, Gioacchino; Di Mario, Francesco; de' Angelis, Gian Luigi (Acta Biomedica Atenei Parmensis, 2018)
Background: The small bowel has often been considered the mysterious “black hole” of the gastrointestinal tract. With regards to this, the development of the wireless capsule endoscopy (WCE) has represented a turning point. It is a non-invasive technique, enabling an excellent visualization of the small bowel (SB) mucosa without the use of radiation. The WCE was approved by the Food and Drug Administration (FDA) in 2001 for adults and in 2004 for children. The aim of the present review is to provide an update on indications, diagnostic yield, safety and limitations of WCE in children. Even though literature regarding the use of WCE in pediatric age is more limited than in adults, WCE is a useful and safe diagnostic tool for the exploration of the small bowel also in children. The indications for WCE are similar at any age, however the main indication in children is Crohn’s disease (CD), while in the adults is the research of SB bleeding. The main limitation in pediatric age is the possibility for younger children to swallow the capsule. WCE in pediatric is a rapidly advancing technology and has the potential to further transform the evaluation and management of SB disease.